Africanidades no processo formativo de professores de matemática - Tivane, Elísio Machikane (2019)
The present doctoral thesis entitled "Africanities in the Formative Process of Teachers of Mathematics", fits the qualitative research, developing the technique of participant observation. It was developed to help with cultural content in Mathematics for Mozambican teaching and law enforcement nº 10.639 / 03, in Brazil. The objective of this study is to analyze all the phases of the training process of the undergraduate students in Mathematics at the Federal University of Uberlandia, Campus Santa Monica, about the work with African and Afro-Brazilian culture (africanities) in the teaching and learning process of Mathematics, carried out with the help of a community of practice. It tries to answer the problem question: What is the movement of the students in the process of formation of the course of Degree in Mathematics on the educational work with africanities? In order to do so, we investigated the process of initial training of undergraduate students in Mathematics at the Federal University of Uberlandia, Campus Santa Monica, in what concerns the work with Africanities, where the researcher constituted a participant observer. Our theoretical framework of analysis did not obey a rigid basis, where the conversations with the various authors take place along the sections that compose this work and base the perceptions and points of view of the participants and the researcher. The productions of the students (participants) were followed from the discussions of the contents in the classroom of the activities done in the virtual learning environment using the moodle platform of the Federal University of Uberlândia. They produced and applied classes or projects on Africanities in schools. The analysis of these productions gave us important information about their effects on the identities and subjectivities of the participants. These productions occurred in three movements: students' movement in the process of knowledge production in the university, which emphasized having produced knowledge about Africanities in Mathematics; students' movement in the process of applying classes or projects in schools, which showed that they had applied the classes and projects satisfactorily, with good results for students and participants; and the movement of the formative process and the constitution of the identities and subjectivities of the participants towards Africanities in the process of teaching and learning Mathematics, in which, from this experience, the participants had their identities and subjectivities transformed, which culminated in the identities of the students. Diversity, prejudice, racism were worked out in a Critical Mathematics education in the promotion of democracy. The classes and projects produced were related to Ethno mathematics, Mathematical Modeling, History of Mathematics, African Games and Critical Mathematics Education.